2017
DOI: 10.1042/bsr20170917
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase C677T polymorphism and colorectal cancer susceptibility: a meta-analysis

Abstract: The association between methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism and colorectal cancer (CRC) susceptibility has been researched in numerous studies. However, the results of these studies were controversial. Therefore, the objective of this meta-analysis was to offer a more convincible conclusion about such association with more included studies. Eligible studies published till May 1, 2017 were searched from PubMed, Embase, Web of Science, and CNKI database about such association. Pooled o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…The MTHFR polymorphisms result in decreased enzyme activity and then low levels of plasma folate and high homocysteine. Folate takes part in various biochemical reactions to provide or accept one-carbon units [14]. Folate deficiency is likely to develop into cancer, possibly due to DNA structural defects [15].…”
Section: Discussionmentioning
confidence: 99%
“…The MTHFR polymorphisms result in decreased enzyme activity and then low levels of plasma folate and high homocysteine. Folate takes part in various biochemical reactions to provide or accept one-carbon units [14]. Folate deficiency is likely to develop into cancer, possibly due to DNA structural defects [15].…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Zacho, J. et al enrolled 75,000 cases and 93,000 controls for a meta-analysis of the association between the MTHFR rs1801133 polymorphism and overall cancer susceptibility and found that the TT genotype of MTHFR rs1801133 was associated with a decreased risk in CRC patients with lifelong hyperhomocysteinemia and hence hypomethylation [33]. Recently, data from another updated meta-analysis with 37,049 cases and 52,444 controls from 91 case-control studies suggested that the MTHFR rs1801133 polymorphism was related to a reduced risk of CRC, particularly in the Asian population [34]. These data supported the protective effect of MTHFR polymorphism, especially rs1801133, on CRC risk.…”
Section: Discussionmentioning
confidence: 99%
“…Third, hyperplastic and adenomatous polyps have complex and different etiologies. As a genetic effect of MTHFR rs1801133 and rs1801131 polymorphisms has been suggested in the susceptibility to colorectal cancer [6, 11, 33, 34], additional confounding factors such as smoking, drinking, age, sex, and patient features should be adjusted for further investigation of the MTHFR variants in the malignant conversion from colorectal polyp.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of MTHFR polymorphism on cancer risk were controversial. Recent published meta-analysis demonstrated MTHFR C677T polymorphism has an increased risk of breast and esophageal cancer, while a decreased risk of colorectal cancer was detected[ 9 11 ]. Thus, MTHFR polymorphism might play various roles in different type of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…However, in view of the available data, studies on the association between MTHFR C677T polymorphisms and cancer risk have yielded mixed results. Some reports indicated that T allele could protect against cancer, while another studies revealed that subjects carrying T allele have increased susceptibility to cancer[ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%